Links and actuators kinematics of IRb-6 manipulator - Szkodny, Tadeusz (Zielona Góra: Uniwersytet Zielonogórski)
A fundamental problem in industrial robots control concerns algorithms generating reference trajectories. In the papers (Gerke, 1985; Gousenes, 1984; Jacak, 1989; Lozano-Perez, 1983) some generating algorithms based on an arbitrary discretization of the manipulators internal coordinates are suggested. Each point of discretization in the external space approximating a reference trajectory is represented by known discretized internal coordinates of the manipulator.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka